ANALISA DAN PERANCANGAN SISTEM MONITORING PERGERAKAN PESAWAT PADA GROUND CONTROL ATC BERBASIS WEB DIBANDARA XYZ - Maudy Lisa Anggraeni; Hari Purwanto (Fakultas Ilmu Komputer dan Desain - Unsurya, 2022)
The Aircraft Movement Monitoring System at the Web-Based Ground Control Atc is a familiar thing in the LPPNI Public Corporation XYZ branch. But, the problem of irregular and manual storage in monitoring aircraft movements in Ground Control is often an obstacle that must be experienced. The Arrival and Departure data storage of both IFR and VFR using a manual system results in frequent errors. In monitoring the movement of the aircraft was still manual and inputting data Arrival and Departure reports are still using a manual system that requires a lot of accuracy and a very long process. Therefore, the Aircraft Movement Monitoring System at Web-Based Atc Ground Control will be able to solve the problem of monitoring that is still manual and inputting data and provide data reports quickly and accurately. With this research, the authors create a new system using the C ++ programming language that uses application platforms namely Dreamweaver and Sublime Text which will facilitate the process of monitoring, inputting, storing and making Arrival and Departure data reports. Thus this study was able to improve the efficiency and effectiveness in monitoring aircraft movements and database processing on Arrival and departure data at the LPPNI Public Corporation XYZ branch. Â Keywords: Monitoring System, Arrival and Departure, Web, Manual System